Simultaneous Multifrequency (SiMFy) Stimulus: A Novel and Reliable Stimulus for Frequency Tuning of Ocular Vestibular-Evoked Myogenic Potentials - Singh, Niraj Kumar; Ravikumar, Mamatha Hunsur; Maruthy, Sandeep (Journal of the American Academy of Audiology, 2022)
Background Frequency tuning of ocular vestibular evoked myogenic potential (oVEMP) refers to the frequency of tone burst that produces the largest amplitude oVEMP. There is an ever-growing pool of published studies that found the frequency tuning of oVEMP distinctly different in Ménière's disease than the age-matched controls and benign paroxysmal positional vertigo. However, recording oVEMP in response to many frequencies makes an already lengthy vestibular test battery even more cumbersome and time-consuming.Purpose The aim of this study was to develop a novel time-saving stimulus that produces reliable results.Research Design Prospective study.Study Sample The study included 25 young, healthy adults.Data Collection The tone-bursts of 2000, 1500, 1000, 750, 500, and 250 Hz were generated and sequenced in this order to prepare a stimulus for simultaneous multifrequency (SiMFy) oVEMP. The response parameters of SiMFy and conventional oVEMP methods were compared.Results No significant difference in peak-to-peak amplitude and frequency tuning existed between conventional and SiMFy oVEMP (p > 0.05). SiMFy had better test–retest reliability and was less time-consuming than the conventional oVEMP.Conclusions SiMFy is a time-saving and reliable stimulus for obtaining frequency tuning of oVEMP with no compromise on the outcomes. It can be immediately applied in most commercially available evoked potential systems with a facility for loading an external stimulus.
Keywords: stimulus chain; simultaneous multifrequency VEMP; frequency tuning; oVEMP